2023
DOI: 10.1002/cam4.5942
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an EMT‐related gene‐based prognostic signature in osteosarcoma

Abstract: Background The correlation between epithelial‐mesenchymal transition (EMT) and osteosarcoma (OS) has been widely reported. Integration of the EMT‐related genes to predict the prognosis is significant for investigating the mechanism of EMT in OS. Here, we aimed to construct a prognostic EMT‐related gene signature for OS. Methods Transcriptomic and survival data of OS patients were downloaded from Therapeutically Applicable Research to Generate Effective Treatments (TARGET) and Gene Expression Omnibus (GEO). We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Three of the four CpG sites were hypomethylated; one was in a CpG island, and three were associated with a promoter. These CpG sites annotated to genes associated with PFAS related health conditions, including various cancers, cognition, cardiometabolic and cardiovascular health (Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…Three of the four CpG sites were hypomethylated; one was in a CpG island, and three were associated with a promoter. These CpG sites annotated to genes associated with PFAS related health conditions, including various cancers, cognition, cardiometabolic and cardiovascular health (Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…Gong et al reported seven novel EMT-related genes for OS outcome prediction, including CDK3, MYC, UHRF2, STC2, COL5A2, MMD, and EHMT2. A high expression of EMT-related genes was associated with poor overall and recurrence-free survival compared to the low-expressing group [156]. The GSVA and GSEA analysis showed a nine-gene set for EMT, including LAMA3, LGALS1, SGCG, VEGFA, WNT5A, MATN3, ANPEP, FUCA1, and FLNA, as independent prognostic markers for OS patient survival [157].…”
Section: Epithelial-to-mesenchymal Transformation and The Osteosarcom...mentioning
confidence: 98%
“…These pathways also aid in cells' epithelial-mesenchymal transition (EMT), encouraging cancer cell migration, invasion, and metastasis. Hinton and colleagues explained the role of these factors in EMT in the pathophysiology of OS [87][88][89] (Figure 3 and Table 5).…”
Section: Signaling Pathwaysmentioning
confidence: 99%